KASTA SENI KRIYA INDONESIA DALAM PENDEKATAN TEKS DAN KONTEKS - I Ketut Sunarya (Ornamen, 2005)
Kriya and human being as if cannot be separated, even can be said that is human being so there is kriya, so in any context this art always ~uman being life. The complexity of duty of she or he who concern in to translate era in every shape op product, which is needed by that duty is a major job that has to be carried by she or he who in kriyawan.In the development era demands art not just stuck in a place but and arises, kriya also begun to tiuch in self-satisfying of the creator. It tion of critical attude that has to be strived to the society, so kriya open. Means that products of art can make lover of art feel addicted fortable in society life.In a text and context approach, kriya development as a text cannot be ed from context, which is products are born: firs called that mystical gave birth primitive kriya with from follows meanings concept. Kriya ection of human being attude that feel surrounded by mystical power them. Second, classic also called post-modern era, in this era kriya edpeak of development. Third, ontology concept resulted kriya withform filows function, it is a reflection of human being attude that is ore surrounded by mystical power. Â Â Human being is free to study ~y thing and what to kenow the meaning of something. Every prod-resulted is come back to the meaning of function aspect; develop ete physical need or psychologicsl need and economy. Fourth, fuction and a rext that has concept of form follows fun. Human being is not e amazed by nature environment, but capture environment and pro-into new environment. This era results a creative kriya and also can be as kriya art. Fifth, cotemporary kriya that was born to bring a new brave of concept to slling product, creation of contemporery avant radical and sensational. But still shows a technique exlporation intenÂand or materal processing using a high skill.Keyword : follows meaning, follows function, follows fun.